GOOGLE TRANSLATE AND PAPER DICTIONARY ON STUDENTS’ VOCABULARY AT SMK N 2 BUKITTINGGI: A COMPARATIVE STUDY - Leni Afrizola; Lena Sastri; Absharini Kardena; Elsi Amiza (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Vocabulary plays a central role in students’ ability to understand and use English effectively, particularly in vocational education where learners are expected to apply language skills in practical, work-related contexts. This study examines whether there is a significant difference in vocabulary achievement between students who use Google Translate and those who use a paper dictionary during English learning. A comparative quantitative design was employed, involving two groups of tenth-grade students at SMK N 2 Bukittinggi. Ninety students were selected through simple random sampling and divided evenly into a Google Translate group and a paper dictionary group. A vocabulary test consisting of multiple-choice items was administered to measure students’ knowledge of word form, meaning, and use. The test results were analyzed using an independent sample t-test to compare the performance of the two groups. The findings show that the mean score of the paper dictionary group was slightly higher than that of the Google Translate group; however, the difference was not statistically significant. This indicates that both tools provide comparable support for vocabulary learning. The results suggest that the effectiveness of vocabulary acquisition does not depend solely on the type of tool used, but rather on how learners interact with the tool and apply vocabulary in meaningful contexts. The study underscores the value of allowing students to use either resource according to their preferences and highlights the importance of integrating both digital and traditional tools to promote balanced and strategic vocabulary learning in vocational classrooms.